The effect of board of commissioners size on risk management trends - Nita Selvia Rohmayati,; Rachmad Hidayat, (Technium Social Sciences Journal, 2023)
This study aims to obtain empirical evidence of the effect of board size on risk management tendencies. The data collection technique used was a purposive sampling method in order to obtain a sample of 531 manufacturing sector companies listed on the Indonesia Stock Exchange in 2014-2017. The data analysis used is Multiple Linear Regression Analysis. The results of this study are that a large number of boards has no impact on the volatility of company stock returns. However, it is positively related to cash flow volatility proxies.